Literature Study: The Role Of Management Accounting System and Decentralization On Managerial Performance - Larasati Pingkan; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
A high-quality management accounting system provides accurate, timely, and relevant information to support managers in decision-making, planning, and control. Research shows a positive relationship between the quality of management accounting systems and managerial performance. In addition, decentralization, by delegating authority to lower-level managers, allows for faster and more effective decision-making and increases managerial motivation. Effective implementation of these two factors can significantly improve managerial performance and the competitiveness of a company.